Radiation-induced cellular senescence and adaptive response: mechanistic interplay and implications - Haiying Wang; Weijin Zou; Yi Cao (Radiation Medicine and Protection, 2025)
Cellular responses to radiation exposure involve complex and dynamic signaling networks that coordinately regulate cell fate. Senescent cells exhibit irreversible growth arrest and functional alterations, while adaptive response confers cellular protection against subsequent radiation insults. The intricate interplay between the two processes influences radiation resistance and genomic stability, with implications for understanding molecular mechanisms of radiotherapy and cellular stress responses. This review systematically investigates the molecular triggers and signaling pathways underlying radiation-induced cellular senescence and adaptive response, and elucidates the molecular interactions between these phenomena. The findings have significant implications for understanding of cellular stress responses, optimizing radiotherapy protocols, and mitigating radiation-induced cellular dysfunction.